EFFECT OF SUBLETHAL DOSE OF ETHION ON SELECTED BIOCHEMICAL PARAMETERS IN THE KIDNEY OF ALBINO RAT - SACHI DEVI.P,; MALLESWARI.M,; SUNEETHA.Y,; JACOB DOSS.P, (International Journal of Pharma and Bio Sciences, 2014)
Ethion[(O,O,O′,O′-tetraethyl S,S′-methy bis(phosphorodithioate))] an organophosphorous (OP) insecticide was introduced seven decades ago for use on plants and animals as an insecticide, acaricide and ovicide.The aim of present study was to investigate the sub lethal effects of ethion induced alterations in protein metabolism in the kidney of Albino rat. Adult male Albino rats of Wistar strain were orally administered ethion (1/5th of LD50 i.e. 42mg/kg body weight) for 30 days with an interval of 48h. Animals were randomly divided into four groups. The first group served as control. Second group of animals was treated with ethion for 10 days, third and fourth groups of animals were administered for 20 days and 30 days respectively. Total proteins decreased in ethion administered groups while all the parameters studied in the present investigation showed an increase and this increase was more in 30 days when compared to 20 days and 10 days administered groups. All the parameters studied in the present investigation were severely altered in Ethion exposed Albino rats. The severity of the damage was also assessed by histopathological studies.The histological observations of the kidney in the ethion exposed Albino rats reveal flattened tubular cells, normal arrangement of kidney cortical tubules are disturbed, glomeruli are atrophied and are loosely attached in Bowman’s capsule. Vacuoles were also found prominent with loss of glomerulus. The results of the present study suggest that Ethion adversely affects kidney functions leading to its physiological impairment. Ethion might have affected protein metabolism and detoxification system in the kidney. The present study suggests that ethion exerts its toxic effect by altering all the parameters of protein metabolism in the kidney of the albino rat.